THE TRACE-ELEMENTS CD, SB, PB AND ZN OF CU ORE OF THE MASSIVE SULFIDE ORE DEPOSIT ERGANI-MADEN, ELAZIG EASTERN TURKEY - UTLU, F; CELEBI, H; PEKER, I (Gustav Fischer Verlag Jena, 1995)
The investigated Cu ore of Ergani-Maden contains low amounts of Cd, Sb, Pb and Zn. The average values are 27, 38, 10 and 77 ppm for Cd, Sb, Pb and Zn respectively. Cd and Sb are enriched 140 and 185 times respectively in comparision with their clarke values and Pb and Zn are as much as their clarke values. These elements can not be used as path finder in region of Ergani-Maden for the exploration of unexposed mineralizations, have no economic importance and do not bear any risks for environmental pollution. The low values of CaO, K2O, Na2O, Cd, Sb and Pb and high values of FeO, MgO, Cr, Ni and Co are results of hydrothermal alteration (sericitisation and chloritisation). The Ergani-Maden Cu ore deposit is a Cu-class deposit of massive sulphide deposits on the basis of Cu- and Zn-ratios. Correlation analysis do not give any distinct relationships among Cd, Sb, Pb and Zn. This can be concluded as the hydrothermal solutions were not saturated with these elements. However, these elements might as well take as part in chalcopyrite, pyrite and magnetite. The positive correlations of these elements and SO3 show that they preferentially took place sulphides. The concentrations of Cd, Zn and Pb show positive correlations with Cd/Sb-, Pb/Sb- and Zn/Cd-ratios. This can be taken as substitutions of Cd and Pb by Sb, and Zn by Cd during crystallisation. The correlations K-K/Pb and Ca-Ca/Cd are positive and show cogenetic evolutions of Pb-K in K-feldspars and Cd-Ca in plagioclases.